PEMBERDAYAAN ADMINISTRASI DAN PEMETAAN DESA: KOLABORASI MAHASISWA KKM UNIBA DENGAN KELURAHAN DALUNG DALAM MENINGKATKAN PELAYANAN PUBLIK - Aliyudin, Aliyudin; Aisah, Siti; Kharisma, Renny; Rusdianti, Shofia; Nathalya, Chiristine Jessica; Puspa, Rani (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
Regional mapping and administrative digitization are crucial steps in improving the quality of public services at the village level. However, limited resources and technological capacity often hinder their implementation. A community service program by KKM Group 03 students from Bina Bangsa University (UNIBA) in Dalung Village, Serang City, focused on creating printed village maps, digitally transforming domicile certificate administration, and assisting with village service activities. This activity aimed to assist the village in providing accurate visual media for regional data and increasing the efficiency of simple technology-based administrative services. The results demonstrated that collaboration between students and village officials can make a real contribution to public service governance. This program serves as a relevant collaboration model for village and village empowerment